Investigation on impact resistance foamed concrete reinforced by polypropylene fibre - Ahmad Zaidi , Ahmad Mujahid (2013)
Foamed Concrete (FC) needs high strength to prevent dynamic loading, thus it is important to enhance the ductility. Usage the Polypropylene Fibre (PF) examined its contribution in strength of FC on impact resistance. Microstructures were observed that air voids in matrix of FC produce micro-porous that reduce interfacial bonding into matrix and generate micro-crack that may propagation crack growth. Presence of PF in admixture results fibrillation and reduces microcracks. Tensile test was investigated that PF delays crack growth in matrix. In this investigation impact test were conducted using an instrumented drop-weight impact tower. When impactor hits the target surface in free surface condition causes compressive plastic wave transform to be tensile wave. It was affected by tensile strength therefore local effect has not found spalling in crater field. In addition influence of porous in matrix FC has ability to absorb the energy and it was not found distal crack around surface area. Penetration depth results showed FC with PF subjected to impact loading was lower than without FC. Presence of PF increases FC strength and local effect results there was not impression of fragments around distal surface due to brittle crushing.